Fast and Quantitative NMR Metabolite Analysis Afforded by a Paramagnetic Co‐Solute. Issue 43 (11th September 2019) - Mulder, Frans A. A.; Tenori, Leonardo; Luchinat, Claudio
Abstract: NMR spectroscopy is an indispensable technique for the determination of the chemical identity and structure of small molecules. The method is especially recognized for its robustness and intrinsically quantitative nature, and has manifested itself as a key analytical platform for diverse fields of application, ranging from chemical synthesis to metabolomics. Unfortunately, the slow recovery of nuclear spin polarization by spin‐lattice (T1 ) relaxation causes most experimental time to be lost on idle waiting. Furthermore, truly quantitative NMR (qNMR) spectroscopy requires waiting times of 5‐times the longest T1 in the sample, making qNMR spectroscopy slow and inefficient. We demonstrate here that co‐solute paramagnetic relaxation can mitigate these two problems simultaneously. The addition of a small amount of paramagnetic gadolinium chelate, available in the form of commercial contrast‐agent solutions, enables cheap, quantitative, and efficient high‐throughput mixture analysis. Abstract : Have your cake and eat it too : The inherent quantitative nature of NMR spectroscopy is typically sacrificed to achieve sensitivity. It is shown here that the analysis of mixtures by NMR spectroscopy can be both quantitative and time‐effective by using the relaxation enhancement from a paramagnetic co‐solute, in the form of a commercially available gadolinium chelate.